Clinico Radiological Profile And Surgical Outcome Of Congenital Craniovertebral Junction Anomalies Surgery: An Institutional Experience - Ghosh, Tamajyoti; Singh, Binoy (Nepal Journal of Neuroscience, 2025)
Introduction: Congenital Craniovertebral junction (CVJ) anomaly has always proved a surgical challenge due to the complex anatomical location, unique embryological development, high mobility of the joints and its intricate relationship to vital neuromuscular structures. Patients usually presents with myelopathy, neck pain, and functional disability, such as difficulty swallowing and a associated neck deformity. Such patients requires early surgical treatment to prevent irreversible neurological deficit. But usually such patient presents late and sometimes respond late to surgical management offered to them. Due to limited literature available regarding surgical outcomes in patients with pre- operative poor neurological grade. Our study is thus an effort to determine the impact of surgery in neurological outcomes in such patients. Materials and methods: In our study, 32 patients of Congenital CVJ anomalies who underwent surgeries were retrospectively analysed for Demographic data, duration of symptoms, clinical presentation, neuroimagings, type of surgery, complications and post surgical outcome. Results: . Clinical and radiological datas of 28 patients were retrospectively analysed and the patients were followed up for 6 months post operatively. Pre operative Nuricks grade were compared with follow up Nurick grade for any improvement in functional outcome. Other independent variables such as age, sex, time of presentation, clinical features were analysed for any correlation with final functional outcome in such patients. Conclusions: Early surgical intervention has better outcomes in congenital CVJ anomalies patients. However some patients with poor pre operative neurological grade also showed promising functional outcome thus emphasising the role of surgery in such patients.